Implementasi Kebijakan Tambahan Penghasilan Pegawai Pemerintah Kabupaten Yalimo - Royendra Manullang; Ari Juliana; Abner Herry Bajari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze and determine the implementation of the additional employee income policy in the Yalimo Regency Government. This study uses a qualitative descriptive method, data collection through interviews at the Jayawijaya Police. A total of 9 informants were selected as key informants. In conclusion, the implementation of the TPP in the Yalimo Regency Government has been carried out in accordance with the procedures and in accordance with the TPP policy, namely Perbup Yalimo No. 4 / 2022 and the Regulation of the Minister of Empowerment of State Apparatus and Bureaucratic Reform of the Republic of Indonesia No. 65 / 2020. The classification of Additional Employee Income (TPP) in Yalimo Regency is in accordance with the standards for determining job classes that have been set by the government. Control and supervision in the form of sanctions for cutting TPP are ineffective because Perbub Yalimo No. 7/2023 itself does not regulate in detail the sanctions for employees who violate discipline with absence values ​​​​that do not meet the criteria, as a result, this policy weakens other policies, namely Article 11 number 1 of Perbup Yalimo No. 7/2023 concerning the Provision of TPP for ASN in the Yalimo Regency Government Environment. Factors that influence the implementation of additional employee income policies in the Yalimo Regency Government. 1) Human resources, financial resources and supporting resources including facilities and infrastructure have a very large influence on the implementation of additional employee income policies. 2) Disposition in the form of attention from actors or policy implementers in the form of providing incentives or rewards for policy implementers who excel greatly influences the implementation of additional employee income policies in the Yalimo Regency Government. 3) A large bureaucratic structure with a large number of employees and no clarity of duties, this causes waste and decreases performance, but employees have a good level of cooperation. Keywords: Policy Implementation, Additional Employee Income